Alternative mental health clinical placements: Knowledge transfer and benefits for nursing practice outside mental healthcare settings. Issue 17 (23rd June 2020) - Goman, Caitlin; Patterson, Christopher; Moxham, Lorna; Harada, Theresa; Tapsell, Amy
Abstract: Aim and objectives: To explore whether nursing student's experiences at Recovery Camp have impacted their current nursing practices. Background: Recently, there has been a move towards more holistic models of nursing care, which seek to break down barriers of stigmatisation and embrace the tenets of self‐determination, to acknowledge people with lived experiences of mental illness and their ability to manage their recovery. In that regard, future health professionals such as nursing students will need to be educated in a manner that recognises the importance of lived experience. In this paper, we propose that Recovery Camp, an alternative clinical placement setting model, enhances clinical practice in multiple domains and is beneficial for both nursing practitioners and people with lived experiences of mental illness, as well as offering an effective nontraditional alternative to conventional clinical placement opportunities. Methods: This study employed a phenomenological research design, involving individual semi‐structured telephone interviews. The Standards for Reporting Qualitative Research (SRQR) checklist was adhered to. Results: Three main themes were identified from the analysis: (a) engagement, (b) understanding mental health and (c) holistic care. "I definitely look at people with mental health conditions in a different light." At Recovery Camp, participants felt that they had greater opportunities for engagement with people with lived experiences, and through this engagement, their preconceptions of mental illness began to change. Conclusions: Recovery Camp may have facilitated the transfer of knowledge that is more person‐centred among nursing students, consequently impacting their current nursing practices. Relevance to clinical practice: Nurses should be equipped with mental health skills regardless of their career trajectory. While Recovery Camp represents a promising approach to facilitate knowledge transfer, further investigation will be required to determine which other factors are instrumental. This approach may have wider implications for nursing education.